2006
DOI: 10.1523/jneurosci.1746-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Angular Tuning Bias of Vibrissa-Responsive Cells in the Paralemniscal Pathway

Abstract: One of the most salient features of primary vibrissal afferents is their sensitivity to the direction in which the vibrissae move. Directional sensitivity is also well conserved in brainstem, thalamic, and cortical neurons of the lemniscal pathway, indicating that this property plays a key role in the organization of the vibrissal system. Here, we show that directional tuning is also a fundamental feature of second-order interpolaris neurons that give rise to the paralemniscal pathway. Quantitative assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
1
38
1
Order By: Relevance
“…Both of these structures are considered part of the paralemniscal system in that both receive most of their trigeminal inputs from the spinal trigeminal interpolaris nucleus (SpVi) (Bruce et al 1987;Huerta et al 1983;Killackey and Erzurumlu 1981;Pierret et al 2000;Zhang and Deschenês 1997). SpVi neurons display conserved angular preferences when the vectors for angular preference were compared using four angles of deflection (Furuta et al 2006). This is consistent with the idea that the relatively high similarity indices in superior colliculus and second somatosensory cortex reflect the properties of input cells in SpVi.…”
Section: Angular Consistency In Multi-vibrissae Receptive Fieldssupporting
confidence: 56%
See 3 more Smart Citations
“…Both of these structures are considered part of the paralemniscal system in that both receive most of their trigeminal inputs from the spinal trigeminal interpolaris nucleus (SpVi) (Bruce et al 1987;Huerta et al 1983;Killackey and Erzurumlu 1981;Pierret et al 2000;Zhang and Deschenês 1997). SpVi neurons display conserved angular preferences when the vectors for angular preference were compared using four angles of deflection (Furuta et al 2006). This is consistent with the idea that the relatively high similarity indices in superior colliculus and second somatosensory cortex reflect the properties of input cells in SpVi.…”
Section: Angular Consistency In Multi-vibrissae Receptive Fieldssupporting
confidence: 56%
“…Inputs from adjacent vibrissae can evoke different response magnitudes in central neurons with some evoking responses that are similar in magnitude to those evoked by the principal vibrissa and others producing negligible responses (trigeminal ganglion: Lichtenstein et al 1990; principal trigeminal nucleus: Minnery and Simons 2003; Veinante and Deschênes 1999; trigeminal nucleus interpolaris: Furuta et al 2006;VPM: Minnery et al 2003;Simons and Carvell 1989;Timofeeva et al 2004;Po thalamus: Diamond et al 1992;Furuta et al 2006;barrel cortex: Simons 1978;Simons and Carvell 1989; second somatosensory cortex: Kwegyir-Afful and Keller 2004; superior colliculus: Hemelt and Keller 2007). While overall similarity indices were low (Ͻ0.4) in all four brain regions, this may be of little functional consequence if the adjacent vibrissae were contributing little to the activity of the neuron in comparison to the activity evoked by the principal vibrissa.…”
Section: Effects Of Response Magnitudementioning
confidence: 99%
See 2 more Smart Citations
“…Yet, none of the interpolaris or caudalis neurons retrogradely labeled from the PrV were reported to be immunoreactive for GABA or glutamic acid decarboxylase (GAD) (Haring et al, 1990). This is somehow intriguing because singlecell labeling studies already showed that the SpVi projection to the PrV arises principally from small-sized local circuit cells (Jacquin et al, 1989a), and in situ hybridization of the GAD67 mRNA has revealed a large number of small-sized GABAergic cells in the SpVi (Furuta et al, 2006). Moreover, electron microscopic studies already documented a rich network of synaptic contacts with numerous axodendritic and axoaxonic GABAergic synapses in sensory trigeminal nuclei (Ide and Killackey, 1985;Bae et al, 2000Bae et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%